Evaluasi Status Hemoglobin dan Hematokrit Masyarakat Sebagai Indikator Awal Status Kesehatan Masyarakat di Kelurahan Tanjung Duren Selatan - Ajeng Normala; Alexander Halim Santoso; Edwin Destra; Fidelia Alvianto; Linginda Soebrata; Nicholas Setia (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hemoglobin and hematocrit examinations serve as important early indicators of hematological status, reflecting the blood’s capacity to transport oxygen. A decrease in these two parameters leads to anemia, which is often undetected due to minimal early symptoms and low awareness to undergo examinations. This activity was carried out using the Plan-Do-Check-Act (PDCA) approach, by examining hemoglobin and hematocrit levels in adult participants. Capillary blood samples were analyzed using a portable device at the examination location. Education was delivered through leaflets regarding the importance of iron, vitamin B12, and folate intake to support erythrocyte formation. The examination was attended by 104 participants, the majority of whom were women. The average hemoglobin was recorded as approaching the lower limit of normal values, while hematocrit levels showed wide variations. More than half of the participants were classified as having anemia. This high proportion of anemia highlights the urgent need for targeted nutritional education. Hemoglobin and hematocrit screening proves effective as an early detection tool for hematological disorders. Education that is linked to laboratory findings should be prioritized to promote improved dietary patterns, particularly the consumption of iron-rich foods, vitamin B12, and folate, in order to prevent erythropoietic dysfunction and long-term health complications.